Strategic account management as a value co-creation selling model in the pharmaceutical industry - Pilon, Francois; Hadjielias, Elias (My University, 2017)
Purpose: This study aims to explore the dynamics enabling strategic account management (SAM) to function as a value co-creation selling model in the pharmaceutical industry. Design/methodology/approach: Using an inductive qualitative research design, data are collected within 11 industry customers in Canada. This work focuses on hospitals as strategic accounts of pharmaceutical companies, exploring SAM value co-creation in the “hospital-pharmaceutical company” relationship. Findings: The findings suggest the presence of two key dimensions that can enable a value co-creation SAM model in the hospital-pharmaceutical relationship: “customer-tailored value-added initiatives” and “relationship enhancers”. Customer-tailored value-added initiatives explain the activities that are central to the hospital-pharmaceutical company relationship and can lead to the provision of value added that is unique to the hospital. Relationship enhancers explain the activities that can help strengthen hospital-pharmaceutical company relations in the pursuit of enhanced value-added interactions between the two parties. The research demonstrates a cyclical relationship between “customer-tailored value-added initiatives” and “relationship enhancers”, leading to value co-creation through a SAM model. Practical implications: The study informs pharmaceutical industry practitioners on how to improve their value proposition through new, more sustainable selling practices. It offers information on implementing a value co-creation SAM model, which can enable pharmaceutical companies to sustain long-lasting value-added relationships with key accounts such as hospitals. Originality/value: The study contributes to the field of SAM by conceptualizing SAM as a value co-creation system. It introduces new knowledge in pharmaceutical marketing by offering empirical insight on the applicability and use of SAM in the hospital-pharmaceutical company dyad.
Keywords: Business-to-Business marketing; Buyer-seller relationship; Pharmaceutical industry; Strategic account management; Value co-creation